Artificial intelligence literacy and foreign language confidence among university second language learners - Ashraf Ragab Ibrahim; Hesham Ramadan Abdo; Mohammad Cherif Boraai; Mohamed Ebrahim Khalf; Mohamed Ali Nemt-allah; Hamed Samy Ghareib (International Journal of Evaluation and Research in Education (IJERE), 2026)
This quantitative correlational-predictive study investigated the relationship between artificial intelligence (AI) literacy and foreign-language confidence among university second-language learners. Two samples were recruited: a psychometric sample (N=341) for scale validation and a main sample (N=541) for hypothesis testing. Participants completed the artificial intelligence literacy scale (AILS), measuring awareness, usage, evaluation, and ethics dimensions, and the foreign language confidence scale (FLCS), assessing foreign language competence, sense of linguistic security, and sense of linguistic ownership. Pearson correlation analyses revealed statistically significant positive associations between all AI literacy and foreign language confidence dimensions (r=.398–.574). Simple linear regression demonstrated that AI literacy significantly predicted foreign language confidence (F(1, 539)=270.742, p